Transport of crude oil and associated microbial populations by washover events on coastal headland beaches. (May 2018) - Curtis, David; Elango, Vijaikrishnah; Collins, Autumn W.; Rodrigue, Matthew; Pardue, John H.
Abstract: Storm-driven transport of MC252 oil, sand and shell aggregates was studied on a low-relief coastal headland beach in Louisiana, USA including measurement of alkylated PAHs and Illumina sequencing of intra-aggregate microbial populations. Weathering ratios, constructed from alkylated PAH data, were used to assess loss of 3-ring phenanthrenes and dibenzothiophenes relative to 4-ring chrysenes. Specific aggregate types showed relatively little weathering of 3-ring PAHs referenced to oil sampled near the Macondo wellhead with the exception of certain SRBs sampled from the supratidal environment and samples from deposition areas north of beach. Aggregates mobilized by these storm-driven washover events contains diverse microbial populations dominated by the class Gammaproteobacteria including PAH-degrading genera such as Halomonas, Marinobacter and Idiomarina . Geochemical assessment of porewater in deposition areas, weathering observations, and microbial data suggest that storm remobilization can contribute to susceptibility of PAHs to biodegradation by moving oil to beach microenvironments with more favorable characteristics. (149). Graphical abstract: Highlights: Storm-driven transport of MC252 oil, sand and shell aggregates was studied including chemical and microbial composition. Aggregates types showed little weathering of 3-ring PAHs exceptthose sampled from the deposition areas north of the beach. Mobilized aggregates contains diverse microbial populations, dominated by the class Gammaproteobacteria . Porewater chemistry, PAH and microbial data suggest thatstorm remobilization can contribute to biodegradation susceptibility.